0 рейтинг
4 видели

упростить 1. 19 cos^2 x - 9 + 19 sin^2 x

2. 17 cos^2 x - 5 + 17 sin^2 x

3. (sin^3 x - cos^3 x) / (1 + sinxcosx) +cosx - sinx

назад (26 баллов) в разделе Алгебра | 4 видели

Всего ответов: 1

0 рейтинг

1. 19 cos^2 x - 9 + 19 sin^2 x=19(cos^2(x)+sin^2(x))-9=19-9=10

2. 17 cos^2 x - 5 + 17 sin^2 x=17(cos^2(x)+sin^2(x))-5=17-5=12

3. (sin^3 x - cos^3 x) / (1 + sinxcosx) +cosx - sinx=

= [(sinx-cosx)(sin^2(x)+sinxcosx+cos^2(x))/(1+sinxcosx)]+cosx-sinx=

= [(sinx-cosx)(1+sinxcosx)]/(1+sinxcosx)]+cosx-sinx=sinx-cosx+cosx-sinx=0

назад Одаренный (1.3k баллов)
10,984,878 заданий
13,471,016 решений
8,518,553 комментариев
4,909,216 пользователей